A comparison of physiotherapy students' perception about blended learning with online learning during COVID-19 pandemic: A mixed method of study - Narasimman Swaminathan; Latha Ravichandran; Sivakumar Ramachandran; Steve Milanese (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The COVID-19 pandemic has affected face-to-face teaching across the globe. The sudden shift in learning methods has impacted learning experiences significantly. Students' perception about online compared to blended learning might affect learning. The objective of this study was to evaluate physiotherapy students' perception of blended compared to online learning. MATERIALS AND METHODS: This mixed-method study documents physiotherapy students' perception about the courses delivered through blended learning (BL) mode during the COVID-19 pandemic. Physiotherapy graduates and postgraduate students who completed their evidence-based physiotherapy practice courses at Sri Ramachandra Institute of Higher Education and Research, Chennai (N = 68) participated in this study. The participants' perceived experience about synchronous online mode and BL during the pandemic was assessed using a questionnaire and focus group discussion. RESULTS: All the participants felt that the course outcomes were met and that they gained knowledge and skills in evidence-based practice. Most of the students (93%) recommended a blended mode of learning compared to online learning alone. Thematic analysis of the focus group discussion (FGD) identified enhanced learning experience, collaborative learning as enablers to BL, and availability of gadgets and quality of online contents as barriers. CONCLUSION: Participants showed par preference for blended learning over online learning as it provided flexibility and facilitated active learning compared to online learning alone.